2014
DOI: 10.1007/s10549-014-2850-9
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing factors associated with women’s attitudes and behaviors toward screening mammography using design-based logistic regression

Abstract: We examined the factors associated with screening mammography adherence behaviors and influencing factors on women's attitudes toward mammography in non-adherent women. Design-based logistic regression models were developed to characterize the influencing factors, including socio-demographic, health related, behavioral characteristics, and knowledge of breast cancer/mammography, on women's compliance with and attitudes toward mammography using the 2003 Health Information National Trends Survey data. Findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 30 publications
3
54
0
Order By: Relevance
“…The study also showed that more than three quarters (78%) of all participants lived in Wrocław, probably because large urban centers tend to provide better access to healthcare resources. This observation is consistent with the findings of many previous studies conducted both in Poland and abroad [17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study also showed that more than three quarters (78%) of all participants lived in Wrocław, probably because large urban centers tend to provide better access to healthcare resources. This observation is consistent with the findings of many previous studies conducted both in Poland and abroad [17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 93%
“…Studies conducted in various countries have shown that health behaviors depend on a number of social and demographic factors, such as age, education, marital status, family situation, social class, and material conditions [17][18][19][20][21]. This article focuses specifically on the age, education, occupational status, and place of residence of screening participants under study.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence at the ecological and individual level from Europe and North America suggests that socioeconomic deprivation, often in conjunction with specific ethnicity, is strongly associated with non-participation in breast cancer screening 11, 12, 13, 14, 15, 16. Transport issues and difficulties in getting to the screening appointment are cited as reasons for non-participation 12, 14.…”
Section: Discussionmentioning
confidence: 99%
“…The potentially significant impact that social support can have on breast cancer detection, treatment, and survival has been well described [45][46][47]. Married women are also more likely to participate in breast cancer screening compared to their unmarried counterparts [48][49][50]. J Womens Health Gyn 2016 | Vol 3: 104…”
Section: Discussionmentioning
confidence: 99%